Healthy centenarians show high levels of circulating interleukin-22 (IL-22) - Basile, Giorgio; Paffumi, Isidora; D’Angelo, Anna Grazia; Figliomeni, Paolo; Cucinotta, Maria Despina; Pace, Elisabetta; Ferraro, Maria; Saitta, Salvatore; Lasco, Antonino; Gangemi, Sebastiano (Archives of gerontology and geriatrics, 2012)
Aging is characterized by a progressive alteration of homeostatic mechanisms modulated by environmental and genetic factors. It is associated with a pro-inflammatory status. In centenarians, an increase of pro-inflammatory cytokine production balanced by anti-inflammatory immune response that would promote longevity is observed. Cytokine dysregulation is believed to play a key role in the proposed remodeling of the immune-inflammatory responses accompanying old age. IL-22 is a pro-inflammatory cytokine belonging to the IL-10 family and represents an important effector molecule of activated T helper (Th)-22, Th-1, and Th-17 cells. We recruited 17 healthy centenarians (4 males, 13 females, range 100–105 years). All ultralongeval subjects were living at home or in a nursing home. Sixteen healthy, sex-matched individuals (4 males, 12 females, range 60–95 years) were also recruited as controls. Centenarians displayed significantly higher circulating IL-22 levels compared to control population (45.7±66.9pg/ml versus 11.1±6.5pg/ml; p=0.031). It's well known that IL-22 is a pro-inflammatory cytokine produced by activated T lymphocytes and NK cells. IL-22 stimulates the production of acute phase reactants and promotes the antimicrobial defense. The results of the present study show, for the first time, that there is an increase of IL-22 in healthy centenarians. This pro-inflammatory condition probably is protective against infection, promoting the longevity of these subjects.